Effects of salt water irrigation at the ripening stage on yield and quality of grown-in-substrate mini-watermelon (Citrullus lanatus) within an arched shed - Di Feng; Yu Cui; Guangmu Tang; Gang Cao; Jiao Chen; Yanhong Ding; Jinxin Wang; Chunhui Ge; Wanli Xu (Agricultural Water Management)
Water scarcity stands as one of the pivotal factors impeding agricultural development. To investigate the impacts of salt water irrigation on crop yield and quality in greenhouse substrate cultivation in regions characterized by freshwater shortages yet abundant salt water resources, this study conducted a two - year experiment with mini-watermelon as the research object. During the ripening stage of mini-watermelon, seven salinity treatments, namely 1.0 (freshwater), 2.6, 4.2, 5.8, 7.4, 9.0, and 10.6 dS·m−1, were established and labeled as CK, T1, T2, T3, T4, T5, and T6, respectively. The research explored how the yield, quality, and ion content in various organs of mini-watermelon responded to salt water irrigation. The results indicated that salt water irrigation at levels ranging from 1.0 to 10.6 dS·m−1 during the ripening stage had no significant impact on growth indices such as vine length and dry matter weight, nor did it affect the yield. Although salt water irrigation did not significantly influence the soluble sugar and soluble solid content of mini-watermelon, it led to a reduction in Vitamin C content (14.7 %–73.2 %) and nitrate content (16.3 %–45.8 %). Compared with the CK treatment, under all salt water irrigation treatments, the Na+ content in different organs of mini-watermelon showed an increasing trend (34.4 %–621.1 %); the K+ ion content increased to varying degrees in fruits (6.5 %–61.0 %), stems (5.8 %–38.6 %), and leaves (30.3 %–98.1 %), but decreased in roots (7.5 %–39.9 %). The Ca2+ ion content exhibited an upward trend in leaves (108.5 %–242.5 %) and fruits (15.6 %–41.4 %), while decreasing in roots (7.5 %–36.1 %) and stems (8.8 %–23.5 %), suggesting that salt water irrigation affects the ion distribution in different organs of mini-watermelon. In summary, the findings suggest that salt water irrigation up to 10.6 dS·m−1 during the ripening stage impacts the ion distribution in various plant organs, maintains yield and quality comparable to freshwater irrigation, and saves more than 20 % of freshwater.